2020
DOI: 10.1007/s00253-020-10644-6
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Yarrowia lipolytica-based consolidated biocatalyst through synthetic biology approach: transcription units and signal peptides shuffling

Abstract: Nowadays considerable effort is being pursued towards development of consolidated microbial biocatalysts that will be able to utilize complex, non-pretreated substrates and produce valuable compounds. In such engineered microbes, synthesis of extracellular hydrolases may be fine-tuned by different approaches, like strength of promoter, type of secretory tag, and gene copy number. In this study, we investigated if organization of a multi-element expression cassette impacts the resultant Yarrowia lipolytica tran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 65 publications
1
12
0
Order By: Relevance
“…Despite some lack of evidence for estimating the risk of reshuffling problems when using repeated sequences, the research teams who developed toolboxes for Y. lipolytica engineering tend to privilege the use of different promoters and terminators as multiple TU elements in order to minimize the possibilities for homologous recombination. Interestingly, a recent process development study using a starch-utilizing GM Y. lipolytica for lipid production suggested that, beside TU design itself, the positional order of multiple TUs was an additional factor to be considered for optimized results [189].…”
Section: Multiple Transcription Unit Vectors In Vitro Dna Assembly Methods and Y Lipolytica Toolboxesmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite some lack of evidence for estimating the risk of reshuffling problems when using repeated sequences, the research teams who developed toolboxes for Y. lipolytica engineering tend to privilege the use of different promoters and terminators as multiple TU elements in order to minimize the possibilities for homologous recombination. Interestingly, a recent process development study using a starch-utilizing GM Y. lipolytica for lipid production suggested that, beside TU design itself, the positional order of multiple TUs was an additional factor to be considered for optimized results [189].…”
Section: Multiple Transcription Unit Vectors In Vitro Dna Assembly Methods and Y Lipolytica Toolboxesmentioning
confidence: 99%
“…These new GG-compatible secretion signals constitute valuable additions to the global Y. lipolytica molecular toolbox. They were notably used in a synthetic biology study in which a TU and signal peptides shuffling approach allowed the optimization of a starch-utilizing GM Y. lipolytica strain for lipid production [189].…”
Section: Targeting the Secretion Pathway: Secretion Signals And Surface Display Systemsmentioning
confidence: 99%
“…Despite some lack of evidence for estimating the risk of reshuffling problems when using repeated sequences, the research teams who developed toolboxes for Y. lipolytica engineering tend to privilege the use of different promoters and terminators as multiple TU elements in order to minimize the possibilities for homologous recombination. Interestingly, a recent process development study using a starch-utilizing GM Y. lipolytica for lipid production suggested that, beside TU design itself, the positional order of multiple TUs was an additional factor to be considered for optimized results [ 226 ].…”
Section: A Brave New World Of Engineered Strains: Tools and Strategies For Building Y Lipolytica Cell Factoriesmentioning
confidence: 99%
“…The Cre-lox recombination system from bacteriophage P1 has been used at INRA to design a user-friendly system for gene deletion and marker rescue in Y. lipolytica : any integrated loxP-bordered marker TU can be efficiently excised through transient expression of the heterologous Cre recombinase using a replicative vector [ 215 ]. Different loxP-excisable markers have been included in some of the newly developed Y. lipolytica toolboxes, the two EasyCloneYALI toolkits [ 226 ] and the Golden Gate toolkit CRISPR tools [ 260 ]. Alternatively, marker rescue can be obtained through a blaster cassette strategy, by making use of the enhanced HR rate of a Δ Ku70 genetic background to allow the use of short repeated DNA bordering sequences for excising a marker for which a counter-selection is available.…”
Section: A Brave New World Of Engineered Strains: Tools and Strategies For Building Y Lipolytica Cell Factoriesmentioning
confidence: 99%
“…The amylase was proved to act on rice, amaranth, and pea starches in raw state and a broad panel of liquefied starches of various plant origin. The knowledge gained from those studies was applied in the following rationale-driven optimization of Y. lipolytica –based consolidated biocatalyst through combinatorial cloning of different signal peptides and changing positional order of the α-amylase and glucoamylase genes in double gene expression cassettes (Celińska et al 2020 ). The aforementioned insect α-amylase was cloned in tandem with Thermomyces lanuginosus glucoamylase having industrially relevant characteristics (Favaro et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%